2021
DOI: 10.1371/journal.pone.0248992
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and associated factors of diabetes self-management: Results of a latent class analysis in a German population-based study

Abstract: Objective Few studies on diabetes self-management considered the patterns and relationships of different self-management behaviours (SMB). The aims of the present study are 1) to identify patterns of SMB among persons with diabetes, 2) to identify sociodemographic and disease-related predictors of SMB among persons with diabetes. Research design and methods The present analysis includes data of 1,466 persons (age 18 to 99 years; 44.0% female; 56.0% male) with diabetes (type I and II) from the population-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…They found that the typology from the study provides important insights for prevention strategies within diabetes health care. 30 A recent study identified three latent classes based on subtypes of dietary behavior and examined the association between class membership and cardiometabolic risk factors. The authors suggested the LCA-driven obesity phenotypes are helpful in assessing and managing obesity and metabolic syndrome by providing interventions tailored to the needs of participants in each class.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the typology from the study provides important insights for prevention strategies within diabetes health care. 30 A recent study identified three latent classes based on subtypes of dietary behavior and examined the association between class membership and cardiometabolic risk factors. The authors suggested the LCA-driven obesity phenotypes are helpful in assessing and managing obesity and metabolic syndrome by providing interventions tailored to the needs of participants in each class.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical methods such as latent class analysis (LCA) provide a useful approach for exploring underlying heterogeneity in a population by allowing researchers to examine whether and how multiple characteristics co-occur to form profiles [ 17 , 18 ]. While LCA has been used to explore patterns of diabetes self-management behavior [ 19 ] and behavioral risk factors for developing diabetes [ 18 ], to our knowledge, it has not been used to understand typologies of people who do and do not use DHTs. The co-occurrence of different factors could represent different profiles of DHT adopters and non-adopters, each of which may need different types of support to use the tools.…”
Section: Introductionmentioning
confidence: 99%